Pengembangan E-Modul Pembelajaran Perawatan Rambut Secara Basah (Creambath) pada Mata Kuliah Perawatan, Pratata, dan Penataan Rambut (P3R) - Dinda Afia Artanti; Sri Irta Widjajanti; Lilis Jubaedah (Departement of Mathematics Education, 2024)
The development of the Wet Hair Care E-Module (creambath) in this study was developed with the Canva application. The Canva application is an application used to create web link-based designs. The Wet Hair Care E-Module (creambath) refers to the CPMK (Course Learning Outcomes) in the Treatment, Pre-styling, and Hair Styling courses. The purpose of this research is to produce a learning medium for the E-Module of Wet Hair Care (creambath) that is suitable for use. This research uses the Research and Development (R&D) method with a 4D development model, namely Define, Design, Develop, and Disseminate. The data collection technique used in this study is a questionnaire as an assessment of validation tests by material and media experts, as well as practicality tests by 5 small group students, and 20 field group students. The results of this study show that the results of the fisrt stage of material expert validation test are 57% and the second stage level 81%, the fisrt stage media expert validation test is 86.7% and the second stage level is 95.5% with the